2023
DOI: 10.1037/tra0001154
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how positive and negative social exchanges relate to posttraumatic stress disorder severity among previously deployed men service members/veterans.

Abstract: Objective: Research in civilians and women shows negative social support is more deleterious for posttraumatic stress disorder (PTSD) symptoms than are the buffering effects of positive social support. However, this is understudied in male military samples. Moreover, appraisals of social support appear to be the mechanism of the association of social support type and PTSD severity, but appraisals as mediators have not been explored in military samples. Method: Previously deployed male service members/veterans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These results are consistent with studies which have found child neglect has a stronger effect on adult depression (Merrick et al, 2017 ) and serious suicide attempts (De Araújo & Lara, 2016 ; Merrick et al, 2017 ) than child physical or sexual abuse. Further, negative perceived social support, including neglect, has been directly linked to greater PTSD symptom severity in military veteran men (Blais & Zalta, 2023 ). Experience of child neglect, rather than child physical or sexual abuse or household challenge, may be particularly salient for the development of adult anger in military veteran men.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with studies which have found child neglect has a stronger effect on adult depression (Merrick et al, 2017 ) and serious suicide attempts (De Araújo & Lara, 2016 ; Merrick et al, 2017 ) than child physical or sexual abuse. Further, negative perceived social support, including neglect, has been directly linked to greater PTSD symptom severity in military veteran men (Blais & Zalta, 2023 ). Experience of child neglect, rather than child physical or sexual abuse or household challenge, may be particularly salient for the development of adult anger in military veteran men.…”
Section: Discussionmentioning
confidence: 99%
“…NSE can include hurtful or insensitive comments from friends, family or strangers; hostile interactions between retail workers and customers; and other interactions wherein an individual is yelled at, ridiculed, made fun of or feels taken advantage of. Interactions characterized by NSE are associated with a range of negative physical health symptoms and mental health outcomes, including depression and loneliness (Tsai et al , 2019), PTSD symptom severity (Blais and Zalta, 2023), drug cravings among recovering opioid users (Knapp et al , 2021) and NSE may even impact the rate of symptoms change in cognitive behavioral therapy for depression (Eidelman et al , 2018). Unfortunately, there is a paucity of research examining the role of NSE as a contributor to suicidal thoughts and behaviors (Blais et al , 2021).…”
Section: Negative Social Exchange As a Contributor To Suicidal Ideationmentioning
confidence: 99%
“…Keywords revictimization, sexual assault, military, gender, posttraumatic stress symptoms, posttraumatic cognitions Posttraumatic stress disorder (PTSD) is one of the most prevalent mental health disorders among Veterans Affairs (VA)-enrolled veterans (Veterans Health Administration, 2013) and active duty service members (Meadows et al, 2018), accounting for over 55% of those with a probable mental health diagnosis (VA, 2017). PTSD and posttraumatic stress symptoms (PTSS) are associated with lower quality of life (Vogt et al, 2017), sexual dysfunction , poorer interpersonal functioning (Blais, 2020(Blais, , 2022Blais & Zalta, 2023), substance misuse (Schumm & Chard, 2012), and suicidal ideation and attempts (Wisco et al, 2014), highlighting the importance of continuing to study risk factors of PTSS to fine-tune assessments and treatments. Traumas that involve sexual violation are associated with the highest risk for PTSS (Blais et al, 2020;Wisco et al, 2014), with repeated exposure conferring even greater risk (see review, Classen et al, 2005;Tirone, Bagley et al, 2020a).…”
mentioning
confidence: 99%